Studi kasus : Asuhan Keperawatan Pada Pasien dengan Harga Diri Rendah - Hafsah Welemuly; Sri Nyumirah (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2022)
Background: Low self-esteem is a negative feeling experienced by an individual towards himself. The emergence of low self-esteem is the result of biological, psychological and social factors which are characterized by a lowered body posture, a feeling of not having positive strengths or abilities, no eye contact, speaking slowly. The impact of low self-esteem is that individuals will tend to be alone, avoid crowds, feel anxious, and feel anxious. Based on data from the yearbook report of dr. H. Marzoeki Mahdi in 2021, the number of patients with paranoid schizophrenia both outpatient and inpatient care is 1144 people with 815 men and 329 women. Purpose: The purpose of this writing is to gain real experience in caring for patients with low self-esteem. Method: This study uses a case study approach through the management of nursing care in patients with impaired self-concept: low self-esteem. Result: this research was conducted in the Bratasena room RSJ dr. H. Marzoeki Mahdi Bogor in January 2022 for three days. Data collection was carried out through observation and interview techniques. Based on the study, several nursing problems were found, namely low self-esteem, social isolation, risk of violent behavior. Conclusion: The expected evaluation from this case study is that patients can have a positive self-concept, an increase in the ability to increase self-esteem followed by a decrease in signs and symptoms.